Hypoxia Activates FGF-23-ERK/MAPK Signaling Pathway in Ischemia-Reperfusion-Induced Acute Kidney Injury - Weihua Liu; Miao Lin; Yiping Dai; Fuyuan Hong (Karger Publishers, 2024)
Introduction: Both hypoxia and fibroblast growth factor-23 (FGF-23) are key factors in ischemia-reperfusion (I/R)-induced acute kidney injury (AKI). This study aimed to explore the relationship between hypoxia and FGF-23 in AKI. Methods: An I/R-AKI animal model was established using male BALB/c mice. HK-2 cells, a part of the human proximal tubular epithelial cell line, were subjected to hypoxia/reoxygenation (H/R). qPCR was used to measure FGF-23 and HIF1α, and ELISA was used to measure inflammatory and oxidative stress cytokines. Western blotting was used to measure the phosphorylation of extracellular signal-regulated kinase (ERK) level. Results: In I/R mice, the levels of interleukin-6 (IL-6), tumor necrosis factor (TNF-α), malondialdehyde (MDA), and the phosphorylation of ERK (p-ERK) were increased, whereas the levels of interleukin-10 (IL-10), superoxide dismutase (SOD), glutathione peroxidase (GPx), and klotho were decreased, compared to the sham-operated mice. Silencing the FGF-23 expression in I/R mice normalized the levels of IL-6, IL-10, TNF-α, MDA, SOD, GPx, and p-ERK. In HK-2 cells, hypoxia-reperfusion (H/R) elevated the levels of IL-6, TNF-α, MDA, and p-ERK, but reduced IL-10, SOD, GPx, and klotho levels. Hypoxia induced apoptosis in HK-2 cells, but silencing of FGF-23 expression blocked the effects of hypoxia on cell apoptosis, pro-inflammatory factor levels, oxidative stress response, and p-ERK levels. Conclusion: FGF-23 is a key molecule in AKI, and hypoxia plays a crucial role in AKI by inducing cell apoptosis; however, its role is regulated by FGF-23. FGF-23 affects oxidative stress and the inflammatory response of kidney tissues by activating the ERK/mitogen-activated protein kinase (MAPK) signaling pathway.